Causal effect of lifestyle and metabolic indicator with herpes zoster: a two-sample Mendelian randomization study - Huang, Mingsheng; Liu, Yiheng; Chen, Cheng; Dai, Weiran (Frontiers in Nutrition, 2024)
Background Previous observational studies have reported certain causal relationships between factors such as smoking, alcohol consumption, obesity, physical activity, metabolic disorders, and the incidence of herpes zoster (HZ). However, there is controversy regarding the observed results across different studies. Our objective was to investigate the causal effects of these risk factors on the risk of herpes zoster through a Mendelian randomization analysis using two-sample bidirectional approaches. Methods We conducted two-sample bidirectional Mendelian randomization analyses to explore the causal relationships between different lifestyles, obesity assessment indices, metabolic indicators, and the risk of herpes zoster. All exposure and outcome data were sourced from publicly available data from genome-wide association studies. Results In the inverse-variance weighted (IVW) analysis, body mass index (BMI) (OR: 1.160, 95% CI: 1.030-1.307, P = 0.014), Body fat percentage (BFP) (OR: 1.241, 95% CI: 1.050-1.467, P = 0.011), and whole body fat mass (WBFM) (OR: 1.199, 95% CI: 1.057-1.362, P = 0.005) exhibited positive associations with the risk of HZ. However, usual walking pace (UWP) (OR: 0.498, 95% CI: 0.254-0.976, P = 0.042) demonstrated a significant negative correlation with HZ risk. Other factors including alcohol intake frequency, smoking initiation, smoking status, insomnia, and sleep duration did not show significant causal relationships with HZ. Conclusion Mendelian randomization studies revealed that BMI, BFP, and WBFM are risk factors for HZ. UWP showed a protective effect against HZ. These findings provide